Antiprothrombin antibodies detected in two different assay systems - Bertolaccini, Maria Laura; Atsumi, Tatsuya; Koike, Takao; Hughes, Graham R. V.; Khamashta, Munther A. (Thrombosis and Haemostasis, 2005)
We evaluated the clinical significance of aPT and aPS-PT by testing for the presence of these antibodies in 212 SLE patients and in 100 healthy individuals. Results show that anti-prothrombin antibodies were found in 47% of the patients (aPT in 31% and aPS-PT in 31%). Their presence did not correlate with that of aCL, anti-β 2GPI, LA and/or anti-protein S. IgG but not IgM aPT were more frequently found in patients with thrombosis than in those without. IgG and IgM aPS-PT were also more frequent in patients with thrombosis (venous and/or arterial) than in those without. Levels of IgG aPT and IgG and IgM aPS-PT were higher in patients with thrombosis than in those without. Although aPT and aPS-PT were more frequently found in women with adverse obstetric history than in those without, the differences were not statistically significant. More significantly, 48% of the patients with aPL-related clinical features who were negative for standard tests had antiprothrombin antibodies. We can conclude that aPT and aPS-PT are frequently found in SLE. Their presence is associated with thrombosis, making these antibodies potential markers for the APS. Testing for these antibodies could be of clinical benefit in patients who are negative for the routinely used tests.
Keywords: Antiphospholipid syndrome; pregnancy morbidity; coagulation; thrombosis; lupus anticoagulant